GEOLOGICAL AND GEOPHYSICAL DATA OF “EPSILON” FIELD IN PRINOS OIL BASIN - Mertzanides, Y.; Kargiotis, E.; Mitropoulos, A. (Bulletin of the Geological Society of Greece, 2010)
The Epsilon field, is located at the centre of Prinos oil basin (N. Aegean, Greece), 11 km NW of the island of Thassos and 4 km NW of the Prinos field, the first productive oil field in the Aegean Sea. The taphrogenetic basin of Prinos has been widely studied, due to its hydrocarbon reservoirs. Extensive geophysical survey, started at early 1970 ‘s, led to a number of drilling jobs, which confirmed the existence of hydrocarbons in the area. The combined geological information, derived from the analysis of lithological, stratigraphic and geochemical data of the basin, suggested a structural and depositional model, strongly related to the Miocene tectonics and sedimentation. The new geophysical and drilling data from Epsilon oil field, are correlated to that already known, completing the model of the basin. Pay zone is found to be below an evaporitic sequence, consisting predominantly of salt, with anhydrite, clay and sandstone intercalations. These upper Miocene aged evaporites extend, varying in thickness, throughout Prinos basin. Reservoir consists mainly of sandstone with intercalations of claystone and trace of siltstone. The geology of the structure and the initial productivity, were positive for further drilling operations in Epsilon field.